How Do Blended Biochemistry Classes Influence Students’ Academic Performance and Perceptions of Self-Cognition? - Ren, Guijie; Zhuang, Peiyue; Guan, Xianren; Tian, Keli; Zeng, Jiping (Frontiers in Psychology, 2022)
The flipped classroom is becoming a popular new instructional model in higher education capable of increasing student performance in higher-order learning outcomes. However, the success of a flipped classroom model depends on various supporting elements, and it may not be appropriate for all students and courses. In this study, a new blended Biochemistry classroom model based on Massive Open Online Courses (MOOC) and a "semi-flipped" environment was applied to Biochemistry instruction of Nursing and Clinical Medicine majors. The students’ academic performance and perceptions of self-cognition were used to assess the blended Biochemistry classroom. Students who participated in the blended classroom model achieved higher academic performance (p<0.01) and reported a significant improvement in their perceptions of self-cognition (p<0.05) compared to the control group. Moreover, the effectiveness of the blended Biochemistry classroom on the small size class (Nursing major) was stronger than on the large size class (Clinical Medicine major).